(untitled) (Revista Contexto & Saúde, 2023)
Introduction: Among the diversity of therapeutic interventions available to improve the physical fitness of patients with Parkinson’s Disease (PD), little is evidenced about patients at an advanced stage of the disease and among the findings, many studies bring heterogeneous and imprecise results about this group. Objective: To carry out a systematic review with the question: What interventions impact the physical fitness of individuals with PD in advanced stages? Method: systematic review of the literature, which was designed, conducted and recorded (PROSPERO: CRD42020189453). A bibliographic search of articles published between 2015 and 2020 was carried out in the main databases. Randomized controlled trials were included, with individuals with PD of idiopathic origin, in the advanced stage of the disease (Hoehn & Yahr scale 4 and/or 5) and that performed physical exercises as an intervention, under the physical fitness outcome. Results: Three studies were included in the final review, which highlighted aquatic exercises with dual-task activities, treadmill training with body weight support, and activities in the home context. The benefits referred to increased walking distance, improved sitting and standing task, and improved balance during daily activities. Conclusion: There are physical exercises that impact physical fitness, even in advanced stages, but there are few studies with the population of individuals with PD in advanced stages.